The Role of Aquaporin 7 in the Movement of Water and Cryoprotectants in Bovine In Vitro Matured Oocytes - Tania García-Martínez; Iris Martínez-Rodero; Joan Roncero-Carol; Meritxell Vendrell-Flotats; Jaume Gardela; Alfonso Gutiérrez-Adán; Priscila Ramos-Ibeas; Adam Z. Higgins; Teresa Mogas (Animals, 2022)
Aquaglyceroporins are known as channel proteins, and are able to transport water and small neutral solutes. In this study, we evaluate the effect of exposure of in vitro matured bovine oocytes to hyperosmotic solutions containing ethylene glycol (EG), dimethyl sulfoxide (Me2SO) or sucrose on the expression levels of AQP3, AQP7 and AQP9. Moreover, we studied whether artificial protein expression of AQP7 in bovine oocytes increases their permeability to water and cryoprotectants. Exposure to hyperosmotic solutions stimulated AQP3 and AQP7 but not AQP9 expression. Oocytes exposed to hyperosmotic Me2SO solution exhibited upregulated AQP3 expression, while AQP7 expression was upregulated by EG hyperosmotic exposure. Microinjection of oocytes at the germinal vesicle stage with enhanced green fluorescent protein (EGFP) or EGFP+AQP7 cRNAs resulted in the expression of the corresponding proteins in ≈86% of the metaphase-II stage oocytes. AQP7 facilitated water diffusion when bovine MII oocytes were in presence of Me2SO solution but not EG or sucrose solution. However, the overexpression of this aquaporin did not increase membrane permeability to Me2SO or EG. In summary, cryoprotectant-induced increase of AQP3 and AQP7 expression could be one of the mechanisms underlying oocyte tolerance to hyperosmotic stress. Water diffusion appears to be improved when AQP7 overexpressed oocytes are exposed to Me2SO, shortening the time required for oocytes to achieve osmotic balance with cryoprotectant solutions.